38 NOX4, A HOMOLOGUE OF NOX2, REGULATES HYPEROXIA-INDUCED REACTIVE OXYGEN SPECIES PRODUCTION AND ANGIOGENESIS IN HUMAN LUNG ENDOTHELIAL CELLS. (1st March 2006) - Pendyala, S.; Gorshkova, I.; Gorshko, B.; Donghong, H.; Stern, R. K.; Usatyuk, P.; Natarajan, V.
Abstract : Rationale: Nox4, a homologue of Nox2 (gp91 phox ), is involved in ROS production and signal transduction in vascular cells. In human pulmonary artery endothelial cells (HPAECs), mRNA expression of Nox4 is several folds higher compared to Nox2 and exposure of cells to hyperoxia (95% O2, 24 hours) resulted in up-regulation of Nox4 and p22 phox but not Nox1 or Nox3. Nox4 siRNA partially reduced ROS formation and blocked cell motility and capillary tube formation in cells exposed to either normoxia or hyperoxia, suggesting a role for Nox4 in angiogenesis. Methods/Results: In HPAECs and human lung microvascular ECs, expression of Nox4 was several folds higher, as shown by real-time PCR, and exposure to hyperoxia (24 hours) up-regulated Nox4 mRNA as well as protein expression. The localization of Nox4 in HPAECs, as determined by immunofluorescence microscopy with Nox4 antibody, revealed that a majority of the native Nox4 protein was localized near the perinuclear region that stained positive for Golgi marker and a small fraction extended throughout the cytoplasm in internal membrane and vesicular structures. Exposure of cells to hyperoxia (3 hours) caused the Golgi to assume a rounded appearance from a saucer-shaped structure where in majority of Nox4 was colocalized. As hyperoxia-mediated cell motility was attenuated by Nox4 siRNA and was dependent on ROS production, we studied the role of Nox4 in capillary tube formation using matrigel assay. Exposure of HPAECs grown on matrigel to hyperoxia (24 hours) increased the number of capillary tubes compared to normoxia and Nox4 siRNA attenuated the capillary tube formation. Conclusion: Nox4 participates in ROS production and acts as a signaling protein that plays a pivotal role in regulating key EC functions such as migration and capillary tube formation. Supported by NIH RO1 HL 69909 to V. Natarajan.